Adiponectin improves NF-κB-mediated inflammation and abates atherosclerosis progression in apolipoprotein E-deficient mice. Issue 1 (December 2016) - Wang, Xuemei; Chen, Qingjie; Pu, Hongwei; Wei, Qin; Duan, Mingjun; Zhang, Chun; Jiang, Tao; Shou, Xi; Zhang, Jianlong; Yang, Yining
Abstract Background Atherosclerosis is a common pathological basis of cardiovascular disease. Adiponectin (APN) has been shown to have an anti-atherosclerosis effect, and the underlying mechanisms, however, are largely unknown. Nuclear factor κB (NF-κB) has also been regarded as a proatherogenic factor, mainly because of its regulation of a variety of the proinflammatory genes linked to atherosclerosis. It was hypothesized that the inhibitory effects of adiponectin on the atherosclerosis is through the inhibition of NF-κB signaling pathway. Methods We injected adenovirus of Ad-eGFP virus (control group) or the same amount of Ad-APN-eGFP virus (APN group) in ApoE-/- mice tail-intravenously. Blood samples and aorta were executed at 0 day, 4, and 8 week of high-fat diet feeding. Histopathological changes of aortic arch root were detected. Levels of TC, TG, HDL-C, LDL-C were measured. Adiponectin and Matrix metalloproteinases-9 (MMP-9) concentration were detected by enzyme-linked immunosorbent assay. Gene and protein levels of adiponectin, eNOS, IL-6, MCP-1, VCAM-1, and other inflammatory factors were determined. Adiponectin, NF-κB p65 in aortic arch root were determined by immunofluorescence and western blot. Results Transduction of Ad-APN inhibited the formation of atherosclerotic plaque in aorta when compared with control group. The lesion formation in aortic arch root was inhibited significantly (P  < 0.01). Lesion lumen ratio decreased significantly (P  < 0.001). The expression of adiponectin attenuated the increases of serum TC (P  < 0.001), TG (P  < 0.001), and LDL-C (P  < 0.001) induced by the high-fat diet, and the increase in body weight (P  < 0.05). As increasing serum adiponectin, the levels of MMP-9 were significantly decreased (P  < 0.05). The exogenous adiponectin increased the gene expression of the anti-inflammatory factors eNOS (P  < 0.05) and IL-10 (P  < 0.001), and reduced the gene expression of inflammatory factors tumor necrosis factor-α (TNF-α) (P  < 0.001), IL-6 (P  < 0.001), VCAM-1 (P  < 0.05), respectively. Adiponectin effectively inhibited the activation of NF-κB pathway and the expression of NF-κB nuclear protein p65. Conclusions Adiponectin may protect the aorta from atherosclerotic injury by reducing inflammation. The molecular mechanism may involve inhibited the expression of downstream components of NF-κB and its transcription factors.